2012
DOI: 10.1115/1.4005903
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Flow Coefficient and Flow Structure on Rotational Cavitation in Inducer

Abstract: Cavitation instability is a major vibration source in turbopump inducers, and its prevention is a critical design problem in rocket-engine development. As reported by Kang et al., (2009, “Cause of Cavitation Instabilities in Three Dimensional Inducer,” Int. J. Fluid Mach. Syst., 2(3), pp. 206–214), the flow coefficient plays an important role in the onset of cavitation instabilities such as rotating and asymmetric cavitation. At high flow rates, various cavitation instabilities occur; on the other hand, as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…In this paper we hypothesize that there are two routes that can lead to breakdown of ABC and onset of RC. At low cavitation numbers, σ<0.035 for the inducer investigated here, the onset of RC is triggered by the cavity sheet breakoff of a cavitating blade that leads to an incidence swing for the adjacent blade, as indicated by Tani et al [11]. At higher cavitation numbers (σ>0.035) RC is triggered by the tip vortex cavity of one of the non-cavitating blades interacting with the adjacent blade.…”
Section: Figure 1 -Mechanism Of Formation Of Rotatingmentioning
confidence: 85%
See 4 more Smart Citations
“…In this paper we hypothesize that there are two routes that can lead to breakdown of ABC and onset of RC. At low cavitation numbers, σ<0.035 for the inducer investigated here, the onset of RC is triggered by the cavity sheet breakoff of a cavitating blade that leads to an incidence swing for the adjacent blade, as indicated by Tani et al [11]. At higher cavitation numbers (σ>0.035) RC is triggered by the tip vortex cavity of one of the non-cavitating blades interacting with the adjacent blade.…”
Section: Figure 1 -Mechanism Of Formation Of Rotatingmentioning
confidence: 85%
“…Cavitation -adapted from [11] The mechanism of formation and propagation of RC proposed by Tani et al [11] and Iga et al [3] cannot explain entirely the dynamic behavior observed in experiments of four bladed inducers. The dynamic behavior of the inducer under consideration in this study is presented in Fig.…”
Section: Figure 1 -Mechanism Of Formation Of Rotatingmentioning
confidence: 99%
See 3 more Smart Citations